Psoriasis vulgaris: Relationship between oral and periodontal conditions and disease severity (2019)
Psoriasis is distributed across the world with a prevalence ranging from 0.5% to 4.6% [1, 2]. This condition has been associated with other diseases, or comorbidities, such as oral cavity involvement, including oral lesions and periodontal disease, thus reaffirming that this is a systemic disease [3, 4]. Psoriasis is a chronic, inflammatory disease which is characterized by the exaggerated proliferation of keratinocytes as a result of immune system activation through T lymphocytes in focal cutaneous areas [5, 6]. In most cases of psoriasis, oral lesions are associated with the presence of geographic and fissured tongue, although data show an increased frequency of associations with generalized pustular psoriasis [7]. It has been estimated that the actual prevalence of fissured tongue and geographic tongue is 6 - 33% and 1-18%, respectively, suggesting that these might represent different expressions of the same disease [7]. However, there is no consensus of the clinical description of what could be considered an oral psoriatic lesion, oral evaluation, or examination, is not a regular procedure in patients with psoriasis [7, 8]. Oral lesions are generally asymptomatic, although there might be tongue swelling and pain when deep fissures are formed [7, 8]. Furthermore, bad tongue hygiene can cause halitosis and tissue swelling due to the accumulation of food residues in fissures, thus causing burning and stinging, especially after contact. However, this association is debatable because it is not known if such oral manifestations are a symptom of disease severity or represent an expression of the disease itself [8]. On the other hand, periodontal disease is marked by an exaggerated response of the immune system to oral microbiota, making it a chronic inflammatory disease which is mediated immunologically, in which immune cells cause inflammation and cellular destruction [9]. Although the two pathologies are similar from the immunological aspect, some characteristics still render them separate diseases and there is no real association known between them [10, 11]. New research has shown that both psoriasis and periodontal disease have both experienced increased prevalence worldwide, and have been associated with other diseases and comorbidities, thus reconfirming that these are, indeed, systemic diseases [12, 13]. There are no existing reports in the published literature which describe the prevalence and frequency of psoriasis and periodontal disease in Colombia. We considered that it was very important for such clinical data to be available because we believe that appropriate examinations should be carried out on all patients with psoriasis, who may have multiple associated comorbidities. We also believe that such examinations should be performed on a regular basis. Furthermore, it is not yet known if the diagnosis of oral psoriasis should be made when lesions in the oral cavity present by themselves, or only at the same time as skin symptoms develop. Consequently, in this study, we aimed to investigate the association between periodontal diagnosis, microbiological components, the presence of IgG against Porphyromonas gingivalis (P. gingivalis), and the clinical manifestations of psoriasis.